2021
DOI: 10.1186/s43141-021-00271-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a novel single nucleotide polymorphism in IGF2 gene with a negative impact on egg production and body weight in Japanese quail (Coturnix japonica)

Abstract: Background Insulin-like growth factor 2 (IGF2) is one of three hormones that share high structural similarity to insulin. It is involved in several insulin-like growth-regulating and mitogenic activities. This study was conducted to genotype the coding regions of the IGF2 gene in Japanese quail (Coturnix japonica) using PCR-SSCP-sequencing, and to assess the possible association of the polymorphism of these regions with the main egg production traits. A total of 240 female birds with an equal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous research has demonstrated the significant association between polymorphisms in candidate genes and various important traits such as growth, carcass, egg production, and meat quality traits in several animal species ( El-Magd et al, 2017 ; Wu et al, 2017 ; Ali et al, 2021 ). Understanding the specific genetic variations responsible for these traits enables the development of targeted breeding and genetic improvement strategies to enhance productivity and quality in the livestock and aquaculture industries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated the significant association between polymorphisms in candidate genes and various important traits such as growth, carcass, egg production, and meat quality traits in several animal species ( El-Magd et al, 2017 ; Wu et al, 2017 ; Ali et al, 2021 ). Understanding the specific genetic variations responsible for these traits enables the development of targeted breeding and genetic improvement strategies to enhance productivity and quality in the livestock and aquaculture industries.…”
Section: Introductionmentioning
confidence: 99%
“…The turkey IGF-2 mRNA codes for 187-amino-acid precursor protein that share greater than 95% nucleotide and amino acid identity with chicken IGF-2 and 60-70% homology with mammalian IGF-2 sequences (Richards et al, 2005). Numerous studies have found links between IGF-2 gene polymorphism and economic traits in various species (Abo-Al-Ela et al, 2014;Ali et al, 2021;Ramadan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%